FURROW AND DRIP IRRIGATION RATES OF COTTON VARIETY S-8286 (Scientific journal of the Fergana State University, 2025)
The article presents the furrow and drip irrigation rates for upland cotton variety S-8286 by applying traditional and water-soluble fertilizers in the conditions of meadow sierozem soils of Samarkand region. In research, the annual N-200, P-140, K-100 and N-150, P-105, K-75 kg ha-1 of nitrogen, phosphorus, potassium and micro element containing new type of mineral fertilizers were applied 6-7 times under drip irrigation technology in different growth stages. The irrigation time, number, scheme, duration, rate and seasonal irrigation amount were determined in different irrigation technologies, in furrow irrigation system, cotton was irrigated 5 times with irrigation scheme of 1-3-1 during the season, the seasonal irrigation rate was 4882 m3, irrigation durations varied from 15 to 20 hours, irrigation intervals from 19 to 23 days. In the drip irrigation technology, cotton was irrigated 10-11 times during the season with irrigation scheme of 1-(2)3-5-2, and the seasonal irrigation rate was 2675 m3. It was found that 45.2% of water was saved compared to furrow. Irrigation duration varied from 7 to 11 hours, and irrigation intervals from 8 to 11 days.